GIG ECONOMY E GESTÃO ALGORÍTMICA DE RECURSOS HUMANOS: forjando transparência, adequando comportamentos, ampliando o controle (Gestão & Regionalidade, 2025)
Algorithmic HRM is a characteristic aspect of the gig economy and platform work, but its transparency and its effects on workers' behavior are still little explored in the literature. From gig workers interviews (rideshare drivers), this article explored how algorithmic management influences working day, especially in relation to the dichotomy transparency vs. opacity. In so doing, we find three main influences of algorithms on HRM practices: work assignment, remuneration and performance management. We identified that workers have high distrust and uncertainty regarding these practices, which develop in a context of surveillance, punishment and reproduction of inequalities, injustices, and biases. The study expands the discussions on the effects of adopting algorithms for HRM, especially in a domain characterized by precarity and informality of labor relations.